2020
DOI: 10.1002/cbdv.202000647
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Yohimbine‐Type Alkaloids from the Leaves of Rauvolfia vomitoria

Abstract: Two new yohimbine-type monoterpene indole alkaloids, rauvines A and B, and six known derivatives were obtained from the leaves of R. vomitoria. The structures of rauvines A and B were determined by extensive spectroscopic analyses, 13 C-NMR, and ECD calculations. This is the first time to determine the absolute configurations of yohimbine-type N-oxides by quantum chemistry calculations (13 C-NMR and ECD calculations). All the isolates were tested for their cytotoxicity against five human cancer cell lines. Rau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The structures of the five compounds (3-7) from fraction 7, and 14 compounds (8-21) from other fractions were determined by comparing their MS, UV, and NMR data with those reported in the literature. The known compounds were β-carboline (3) (Bratchkova et al, 2012), 1-methyl-β-carboline 4) (Bratchkova et al, 2012), sarpagine (5) (Rukachaisirikul et al, 2017), lochnerine (6) (Kam et al, 1999), vellosiminol (7) (Mbeunkui et al, 2012), tetrahydroalstonine (8) (Achenbach et al, 1997), isoreserpiline (9) (Gupta et al, 2012), 10-methoxytetrahydroalstonine (10) (Gupta et al, 2012), carapanaubine (11) (Khatoon et al, 2022), isocarapanaubine (12) (Ahmad et al, 2010), N a -methylrauflorine (13) (Carlos et al, 2016), venoterpine (14) (Rukachaisirikul et al, 2017), mitoridine (15) (Kumara et al, 2019), yohimbine (16) (Zhan et al, 2020b), ajmaline (17) (Lim et al, 2014), vinmajorine D (18) (Zhang et al, 2016), 17-epivinmajorine D (19) (Zhang et al, 2016), peraksine (20) (Gao et al, 2015), and 17-epi-peraksine (21) (Arthur et al, 1968).…”
Section: Isolation and Structural Elucidation Of The Active Compounds...mentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of the five compounds (3-7) from fraction 7, and 14 compounds (8-21) from other fractions were determined by comparing their MS, UV, and NMR data with those reported in the literature. The known compounds were β-carboline (3) (Bratchkova et al, 2012), 1-methyl-β-carboline 4) (Bratchkova et al, 2012), sarpagine (5) (Rukachaisirikul et al, 2017), lochnerine (6) (Kam et al, 1999), vellosiminol (7) (Mbeunkui et al, 2012), tetrahydroalstonine (8) (Achenbach et al, 1997), isoreserpiline (9) (Gupta et al, 2012), 10-methoxytetrahydroalstonine (10) (Gupta et al, 2012), carapanaubine (11) (Khatoon et al, 2022), isocarapanaubine (12) (Ahmad et al, 2010), N a -methylrauflorine (13) (Carlos et al, 2016), venoterpine (14) (Rukachaisirikul et al, 2017), mitoridine (15) (Kumara et al, 2019), yohimbine (16) (Zhan et al, 2020b), ajmaline (17) (Lim et al, 2014), vinmajorine D (18) (Zhang et al, 2016), 17-epivinmajorine D (19) (Zhang et al, 2016), peraksine (20) (Gao et al, 2015), and 17-epi-peraksine (21) (Arthur et al, 1968).…”
Section: Isolation and Structural Elucidation Of The Active Compounds...mentioning
confidence: 99%
“…It has a long history to treat hypertension, pain, epilepsy, high fever, and gastrointestinal diseases. Previous phytochemical studies of RVA have revealed the presence of a series of monoterpene indole alkaloids (Zhan et al, 2020a;Zhan et al, 2020b), making it a potential source of chemosensitizers. Establishment of a robust analytical technique for rapidly identify the chemosensitizers from RVA is meaningful.…”
mentioning
confidence: 99%
“…Furthermore, yohimbine significantly reduces the levels of dihydrotestosterone, prostatic acid phosphatase, prostate-specific antigen, proliferating cell nuclear antigen, and steroid 5α-reductase, suggesting its beneficial effects against BPH. Several studies reported the cytotoxicity of yohimbine in different human cancer cell lines [ 1 , 104 , 105 ]. Zhan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al. [ 105 ] reported moderate cytotoxicity of yohimbine-type alkaloid containing a β-carbolinium group on human MCF-7 breast, SWS80 colon, and A549 lung cancer cell lines with IC 50 values of 25.5, 22.6, and 26.0 µM, respectively. In addition, Shen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The eponymous member of the family, yohimbine ( 1 ), is a potent pan-subtype α2-adrenergic receptor (α2-AR) antagonist that is a component used in traditional medicines and is a frequent chemical probe of α2-AR activity for various physiological processes . There is a growing body of evidence demonstrating the potent cytotoxic activity of various yohimbinoids and synthetic derivatives of the yohimbine framework . For example, Ma and coworkers determined that yohimbine inhibited the proliferation of two different pancreatic cancer cell lines .…”
Section: Introductionmentioning
confidence: 99%